Kindergarten teachers' attitudes towards the teaching profession and its relationship to years of service (Journal of the College of Basic Education, 2023)
The Arab world is witnessing a scientific and technological revolution, which had a great impact on people's behavior and their dealings with the social and cultural environment in which they live. Education, and the school plays a fundamental role in achieving the goals and missions of education, as it is the institution that works to prepare a good citizen that society needs.The teaching profession has been exposed to many challenges, represented by the shaky social status of the teacher, as the victim who is attributed to the errors of education and its failure to achieve its goals. Or when you made him shabby clothes, a beggar deserving of lamentation instead of presenting him as a thinker, the author of the message (Bashara, 1986: 6), and the result of that was the reluctance of large numbers of students from the profession of teaching (Tarish and Al-Muthin: 152, 1989-151). enrolled, their attitudes were negative.The teacher is considered the key to the educational process and its basis, and accordingly its success or failure is located, and to the extent that the scientific and practical basis is available in its preparation, to the extent that we get a good teacher and thus a good education that leads to a human building capable of progress and prosperity. (Bishara, 1986: 6)Preparing the teacher and preparing him for the requirements of the profession on the one hand, and the requirements of the modern era on the other hand, is one of the educational issues that is receiving increasing attention in many contemporary systems. (Arab Bureau of Education for the Gulf States, 1984, 24)